CHROMOSOME-STUDIES IN MALES AFFECTED BY DUCHENNE OR BECKER MUSCULAR-DYSTROPHY - Batista, DAS; Viannamorgante, A. M.; Zatz, M. (Soc Brasil Genetica, 1990)
We studied cytogenetically 48 male patients with Duchenne or Becker muscular dystrophy. All of them showed normal X chromosomes. Fragility of Xp21 was investigated in 1400 G-banded chromosomes of 28 patients and only one break was observed at this band (0.07%). This low frequency of breakage excludes Xp21 as a fragile site in these patients.